Anxiety symptoms in critically ill COVID-19 survivors and its association with post-discharge health concerns. (1st June 2022) - Silva, B.; Martins, S.; Ferreira, A.R.; Fernandes, J.; Vieira, T.; Fontes, L.; Reis, N.; Braga, A.; Coimbra, I.; Paiva, J.A.; Fernandes, L.
Abstract : Introduction: Evidence suggest that critically ill COVID-19 patients are at higher risk of developing anxiety symptoms, which may be related to or exacerbated by patients concerns regarding their health status and recovery. Objectives: To assess anxiety symptoms in critically ill COVID-19 survivors, 1-2 months after hospital discharge and to analyze its association with concerns reported by patients regarding their own health status and recovery. Methods: In the framework of MAPA prospective research, this preliminary study included COVID-19 patients admitted in the Intensive Care Medicine Department (ICMD) of a University Hospital. Patients were excluded if they had an ICMD length of stay (LoS) ≤24h, terminal illness, major auditory impairment or inability to communicate at the evaluation time. Participants were assessed at a scheduled telephone follow-up appointment, with Generalized Anxiety Disorder Scale (GAD-7). Additional questions were asked to assess the survivors' post-discharge concerns regarding discrimination against for COVID-19, infection of a family member, re-infection or sequelae related to COVID-19. Results: Eighty-three patients were included (median age=63 years; 63% male) and 24% had anxiety symptoms. Anxiety scores were higher in survivors who reported being afraid of being discriminated against for COVID-19 (30% vs 10%; p=0.034), being re-infected (100% vs 79%; p=0.032) and having sequelae (94% vs 44%; p<0.001). Conclusions: These findings revealed that anxiety is common in COVID-19 survivors and is associated with post-discharge patients concerns that may limit patient daily living. This study emphasizes the importance of psychological assessment and follow-up of the COVID-19 survivors, in order to support these patients recovery. Disclosure: No significant relationships.